An assessment of chat reference service usage patterns and trends at the Rizal Library, Ateneo de Manila University and the University of the Philippines Diliman Main Library - Bagunu, Jessie Rose M. (2011)
This study is an assessment of the chat reference service usage patterns and trends of the Ateneo de Manila University-Rizal Library and University of the Philippines-Main Library. Through quantitative measures, the study included the use of log and report analysis, descriptive statistics, content analysis and the quality of chat reference transaction.